Creación de empresa dedicada a la prestación de servicios de dirección artística de proyectos a nivel local y nacional (2020)
Rose Gold Agency, is an advertising agency dedicated to directing artistically medium and large companies in the fashion and beauty sector, aimed at all brands that want to improve the image and identity of their organization, obtaining as a result audiovisual and photographic content inspired by haute couture and editorial concept of European taste using alternative models to beauty prototypes. Consumers today work with feelings, they want to see themselves reflected or identified with what they consume, so carry out campaigns where real beauty together with haute couture in an editorial context is the protagonist, will help touch emotions and understand brands as a personality and not as a process of consumerism or fast fashion exclusively. Thanks to social networks, the immediacy of global information is within reach of all internet users, or 97% of the world population. The people already have access to all the trends that occur on the planet, for that is important to be at the forefront, especially in the way of selling a product (in this case clothing and makeup). Quality and creative idea define much if a customer loyalty to the brand or not, this generates the need for companies hiring services that produce quality parts and with an idea original. This agency has creativity as a quality in its productions, innovation is the key to online audience retention, using people from day to day in trending product campaigns, they allow consumers to visualize said brand as a reality and not as an imaginary.